Enhanced water transport and salt rejection through hydrophobic zeolite pores. (21st November 2017) - Humplik, Thomas; Lee, Jongho; O'Hern, Sean; Laoui, Tahar; Karnik, Rohit; Wang, Evelyn N
Abstract: The potential of improvements to reverse osmosis (RO) desalination by incorporating porous nanostructured materials such as zeolites into the selective layer in the membrane has spurred substantial research efforts over the past decade. However, because of the lack of methods to probe transport across these materials, it is still unclear which pore size or internal surface chemistry is optimal for maximizing permeability and salt rejection. We developed a platform to measure the transport of water and salt across a single layer of zeolite crystals, elucidating the effects of internal wettability on water and salt transport through the ≈5.5 Å pores of MFI zeolites. MFI zeolites with a more hydrophobic (i.e., less attractive) internal surface chemistry facilitated an approximately order of magnitude increase in water permeability compared to more hydrophilic MFI zeolites, while simultaneously fully rejecting both potassium and chlorine ions. However, our results also demonstrated approximately two orders of magnitude lower permeability compared to molecular simulations. This decreased performance suggests that additional transport resistances (such as surface barriers, pore collapse or blockages due to contamination) may be limiting the performance of experimental nanostructured membranes. Nevertheless, the inclusion of hydrophobic sub-nanometer pores into the active layer of RO membranes should improve both the water permeability and salt rejection of future RO membranes (Fasano et al 2016 Nat. Commun. 7 12762).